THE CASE OF THE MISSING CUTLERY : A LEADERSHIP COURSE for THE RISING STAR - Allen, Kevin, 1954-
A fabulously entertaining ( and true ) tale of a newly minted leader made buoyant during The Case of the Missing Cutlery : A Leadership Course for the Rising Star. For those who might reading about leadership success at the Fortune 50 level inspiring b